Interpretasi Ajaran Gereja Protestan Terhadap Etika Kehidupan Sosial Jemaat Dalam Masyarakat Modern - Nabila Yolanda Siregar; Arifinsyah Arifinsyah (Kamaya: Jurnal Ilmu Agama, 2026)
This research aims to examine the interpretation of Protestant Church teachings on the ethics of social life in modern society, particularly in the context of social transactions between religious communities. This study focuses on three problems, namely: How is the interpretation of Protestant Church social teachings on the ethics of social life in the context of Christian transactions in modern Indonesian society?. How are the dynamics of change historically?, and What are the challenges of its implementation in a pluralistic society. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results show that the Protestant Church interprets moral and social teachings by emphasizing the values ​​of love (agape), justice, solidarity, and tolerance as the basis for forming the congregation's social ethics. This interpretation develops contextually from a normative-institutional approach to a more dialogical and participatory approach in modern social life. In practice, the congregation implements these values ​​through mutual cooperation activities, humanitarian services, community empowerment, and interfaith social cooperation. However, its implementation still faces challenges in the form of increasing individualism, shifts in moral values, and the influence of digital technology on social relationship patterns. Thus, the interpretation of the Protestant Church's social teachings is dynamic in building harmonious social interactions, so that it is necessary to strengthen social ethics education and interfaith dialogue as a strategy to maintain the consistency of the congregation's social practices in the modern era. Therefore, this study recommends strengthening the role of the Protestant Church in fostering the congregation's social ethics as well as increasing dialogue and cooperation between religious communities in order to create a harmonious and just social life and the creation of world peace.